Nagasari (Mesua ferrea): Budidaya dan Potensinya sebagai Tanaman Obat - Yuliah Yuliah; Lukman Hakim; Yayan Hadiyan (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Nagasari (Mesua ferrea) is a plant from the Gutiferae family. The dispersal areas including India, Sri Lanka, Nepal, Indochina, Malaysia, Burma, Thailand, Indonesia, and Papua New Guinea . In Indonesia, the initial spread of Nagasari is estimated to originate from India. In Java and Bali, Nagasari has been cultivated on limited areas, but more are growing wild. The purpose of this research is to review the aspect of Nagasari cultivation and its potential as a medicinal plant through literature studies of journals, proceedings, and popular online media. The results show that the research of Nagasari include many aspects such as germination, breeding, and mating system. Nagasari  has been utilize as a raw material including for medicine because its contents of anti-septic properties, anti-inflammatory, blood cleanser, analgesic, inflammation, rheumatism, laxative and others. Nagasari's research in Indonesia is still very limited compared to similar research abroad. Various studies that have been conducted show the potential of Nagasari to be developed as a medicinal plant. Therefore it is necessary to conduct further studies to understand Nagasari's botanical ethno in a more in-depth comprehensive fund of aspects of cultivation to its use by the community. Measurable research is needed to obtain Nagasari's in-depth information as a medicinal plant by involving related industries.